The Neural Basis of Social Cognition in Typically Developing Children and Its Relationship to Social Functioning - Lincoln, Sarah Hope; Mukerji, Cora M.; Dodell-Feder, David; Riccio, Arianna; Hooker, Christine I. (Frontiers in Psychology, 2021)
Theory of mind (ToM), the ability to think about the perspectives, beliefs, and feelings of another, develops throughout childhood and adolescence and is an important skill for social interactions. This study examines neural activity in typically developing children during a novel ToM task – the Movie Mentalizing Task– and tests its relations to ToM behavioral performance and social functioning. In this fMRI task, children ages 8-13 years (N=25) watched a brief movie clip and were asked to predict a character’s mental state after a social interaction. Engaging in the Movie Mentalizing Task activated the ToM neural network. Moreover, greater neural activity in the ToM network, including the superior temporal gyrus and inferior frontal gyrus, was associated with better behavioral performance on independent ToM tasks and was related to better social functioning, though these results do not survive correction for multiple comparisons. Results offer a new affective theory of mind task for children in the scanner that robustly recruits activity in theory of mind regions.